Pengaruh Kinerja Keuangan dan Ukuran Perusahaan Terhadap Laporan Keberlanjutan (Studi Pada Perusahaan Yang Terdaftar Di BEI Tahun 2018-2022) - Sitohang, Putri; Suhendro, Saring (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to find out and analyze the influence of the variables Profitability, Company Size, Leverage, Liquidity, and Activity on Sustainability Reports in companies listed on the Indonesia Stock Exchange in 2018-2022. The data used in this study is secondary data with sampling techniques carried out by the purposive sampling method. A total of 37 companies were used in this study and 185 samples were obtained. The test was carried out using the logistic regression analysis method with the SPSS 27 test tool. The results showed that Profitability and Company Size had a positive effect on the Sustainability Report, the Leverage variable had a negative effect on the Sustainability Report, while the Liquidity and Activity variables had no effect on the Sustainability Report.